The problem of man in Protestant theology of the twentieth century - Gavrulyuk, Tetyana (Ukrai͏̈ns'ke relihijeznavstvo, 2013)
A characteristic feature of Protestant theology of the twentieth century is a turn to anthropology, the formation of anthropologically oriented theology. The reason for this is the social processes and general tendencies of the philosophical thought of that time. The delineation of religion from the state, the restoration of religion to the personal affairs of man predetermine the need for the understanding of man as a being that transcends to the supernatural. Defining in the conception of supernatural, God - both in philosophy and in theology - now there is not cosmology, but an existential, human experience of existence. In this way, the soteriological issues acquire an individualistic color. Thus, the problems of sin, freedom of will and grace are interpreted in the context of the existence of an individual. Already in the twentieth century, this vector of development of Protestant theology was criticized. Therefore, the formation of Protestant anthropology was carried out in several directions. The study of the main tendencies of Protestant anthropology of the twentieth century is currently relevant, since it can provide a new direction in the search for an exit from the anthropological crisis of our time.